2006
DOI: 10.1103/physreve.73.016111
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous diffusion: Exact solution of the generalized Langevin equation for harmonically bounded particle

Abstract: We study the effect of a disordered or fractal environment in the irreversible dynamics of a harmonic oscillator. Starting from a generalized Langevin equation and using Laplace analysis, we derive exact expressions for the mean values, variances, and velocity autocorrelation function of the particle in terms of generalized Mittag-Leffler functions. The long-time behaviors of these quantities are obtained and the presence of a whip-back effect is analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 19 publications
4
84
0
Order By: Relevance
“…Here we explore a similar scenario for the fractional oscillator, and find rich types of physical behaviors. It is known [12] that in the long time limit all solutions x (i.e. any 0 < α, 0 < γ and 0 < ω ) decay monotonically, some what like the over-damped behavior of the usual oscillator, however now the decay is of power law type.…”
Section: Introductionmentioning
confidence: 99%
“…Here we explore a similar scenario for the fractional oscillator, and find rich types of physical behaviors. It is known [12] that in the long time limit all solutions x (i.e. any 0 < α, 0 < γ and 0 < ω ) decay monotonically, some what like the over-damped behavior of the usual oscillator, however now the decay is of power law type.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, pure power-law correlation functions have been employed to investigate the anomalous diffusion behavior of the particle that is related to the long time tail correlations. [35][36][37][38] Recently, Viñales and Despósito 39 have considered a Mittag-Leffler noise given by…”
Section: Thermostat Described By An 1d Glementioning
confidence: 99%
“…(12) and (13), it follows G(0) = 0 and g(0) = I. Furthermore, similar to the one-dimensional case [30,31], it can be shown that the relaxation function g(t) is identical to the long-time behavior of the normalized velocity autocorrelation function (see the appendix for the detailed derivation):…”
Section: Generalized Langevin Equation With Two Coupled Coordinatesmentioning
confidence: 72%
“…(40)], which features subdiffusive dynamics [31]. Quantities in the WN coordinate, in contrast, exhibit an exponential equilibrium rate [as seen in Eq.…”
Section: Particle Bounded By Harmonic Potentialmentioning
confidence: 99%